Islamic Education within Muslim Minority: A Study of Finnish National Agency for Education (FNAE) Documents - Akhmad Nurul Kawakip; Mohammad Asrori; Moch. Khafidz Fuad Raya; Miftachul Huda; Basori (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
Finland, as a Nordic country with a Muslim minority, seems to place a special position on Islamic education and makes it the same portion as the education of the majority religion such as Lutheran in the Finnish National Agency for Education (FNAE). The existence of 20 Finnish schools officially recognized by the government as having Muslim communities and providing Islamic education is evidence that the development of Islamic education in public schools is growing significantly. This article aims to showcase the Islamic education system in Finland and its management practices from the Islamic education practice documents issued by the FNAE. This study employed the Documentary Research (DR) method to explore primary data. The documents from the FNAE are the basis for all schools in Finland. This article demonstrates that the Principle of Justice regulates the right to religion, including freedom in religious education, the presence of Finnish Muslims in the past made the Muslim community recognized by the state along with the provision of Islamic education, and the position of Islamic education in the FNES is determined by the state where ‘religious education for students is by the religion they adhere to and believe in’. This is what makes Islamic education subjects taught two hours per week for a year, where the curriculum is designed for three contents: students’ understanding of Islam, views on world religions, and living a good life. This article argues that Islamic education in minority countries places the landscape of religiosity and inter-religious equality as state acceptance in organizing religious education for all communities.